Hubungan self-efficacy, self-esteem dan perilaku prokrastinasi siswa madrasah aliyah negeri di Malang Raya - Friska Putrisari; I M Hambali; Dany M Handarini (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2017)
This study aims to determine the relationship between self-efficacy and self-esteem with the student procrastination behavior Madrasah Aliyah in Malang Raya. This study uses measures in a quantitative approach that is research correlation multiple regression. Data analysis were performed with SPSS 23.0 for Windows. The results showed that the relationship between self-efficacy and self-esteem has a significant relationship with p =, 000. Relationships between variables included in the criteria being the value of R =,432. Self-efficacy and self-esteem accounted for 18.7% influence on the behavior of procrastination. Partial calculation showed that the relationship between self-efficacy with procrastination have a very significant with p = .015. Their relationship into low criteria with r = -2.443. While between self-esteem with procrastination have a very significant relationship with p=, 000. Relationships are both included in the high criteria with a value of r = -8.056.